IMPLEMENTATION OF CRIMINAL LAW ENFORCEMENT ON THE MAKING OF FAKE VACCINE CERTIFICATES - Surya Dharma Samosir; Rahmi Ayunda (ConCEPt - Conference on Community Engagement Project, 2022)
The crime of forgery of letters is a crime that essentially contains the essence of untruth or false status of an object. Either that looks from the outside as if it is true when in fact it is very contrary to the real thing or to the truth. The crime of forgery of letters develops in line with things that are happening in the world today, especially during the Covid-19 Pandemic. The reason behind why people want to make a COVID-19 vaccine certificate is that many people want to get the vaccine certificate but don't want to be injected with the vaccine. A COVID-19 vaccine certificate if falsified is very dangerous, it can harm many people, those who have received a COVID-19 vaccine certificate are a sign that they have resistance to the virus. this spreads to a crime on the Vaccine Certificate which is in fact an important thing during the current Pandemic. There are irresponsible parties who commit crimes in the form of issuing Counterfeit Vaccine Certificates in order to benefit themselves but can indirectly harm other people, this is in line with Article 263 of the Criminal Code. In carrying out this research, the author uses a normative juridical method based on a qualitative approach. The author conducts an analysis related to the Juridical Impact of the existence of the Counterfeit Vaccine Certificate by taking into account the Decision of the Panel of Judges in Decision Number: 543/Pid.B/2021/PN Btm. The purpose and benefits of this problem are raised into a writing, namely in order to provide an explanation and understanding of the importance of understanding the law and the author hopes that everyone can understand the crime of this fake letter.